2015
DOI: 10.3171/2015.1.spine14489
|View full text |Cite
|
Sign up to set email alerts
|

Are the standard parameters of cervical spine alignment and range of motion related to age, sex, and cervical disc degeneration?

Abstract: OBJECT The aims of this study were 1) to establish the standard parameters of alignment and total and segmental range of motion (ROM) of the cervical spine in the asymptomatic population, and 2) to identify factors that influence cervical ROM and alignment. METHODS The authors measured 636 standard cervical lateral, flexion, and extension plain radiographs of 212 asymptomatic volunteers. The relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…We used ROM as an outcome measure because current literature suggests that it is restricted in chronic neck pain and that it decreases with age. 42,43,[46][47][48] Normal values for CROM have been reported in asymptomatic participants. 5 In our study, left rotation (20°), right rotation (14°), flexion (12°), and extension (8°) differed most compared with asymptomatic age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used ROM as an outcome measure because current literature suggests that it is restricted in chronic neck pain and that it decreases with age. 42,43,[46][47][48] Normal values for CROM have been reported in asymptomatic participants. 5 In our study, left rotation (20°), right rotation (14°), flexion (12°), and extension (8°) differed most compared with asymptomatic age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…For one study, our results were similar for flexion but not for extension and rotation. 42 This was possibly because that study only included women, who typically have greater ROM, 43 and excluded participants with psychiatric, vestibular, and dizziness complaints. 42 Patients with neck pain, especially those with acute whiplash disorder, are known to have dizziness and sensorimotor impairments due to disturbed cervical spine receptors, 44,45 so we excluded this group; but, some patients may have had a traumatic neck injury that caused dizziness or vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the process of degenerative changes in the cervical spine, including cervical flexion and extension activity, diminish following the emergence of cervical symptoms [ 17 ]. These previous findings are supported by the findings of the present study, which showed that the overall range of movement (ROM) of the cervical spine in the two groups was less than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of cervical lordosis is the most common disorder of sagittal cervical balance. [30,33] Although the sagittal alignment of the cervical vertebrae can vary with age and sex, [8,30] the natural sagittal curve of the cervical spine is known to have a lordosis [7,12,19]. Harrison et al reported a mean C2-C7 lordotic angle of -26.89° ± 9.72° in 72 healthy participants.…”
Section: Introductionmentioning
confidence: 99%
“…Harrison et al reported a mean C2-C7 lordotic angle of -26.89° ± 9.72° in 72 healthy participants. [12] Liu et al demonstrated a mean C2-C7 lordotic angle of -21.40° ± 12.15° in 212 asymptomatic volunteers [19]. The estimated prevalence of loss of cervical lordosis in patients with posterior neck pain is approximately 42%.…”
Section: Introductionmentioning
confidence: 99%